2014
DOI: 10.1186/1687-9856-2014-4
|View full text |Cite
|
Sign up to set email alerts
|

State of the art review in gonadal dysgenesis: challenges in diagnosis and management

Abstract: Gonadal dysgenesis, a condition in which gonadal development is interrupted leading to gonadal dysfunction, is a unique subset of disorders of sexual development (DSD) that encompasses a wide spectrum of phenotypes ranging from normally virilized males to slightly undervirilized males, ambiguous phenotype, and normal phenotypic females. It presents specific challenges in diagnostic work-up and management. In XY gonadal dysgenesis, the presence of a Y chromosome or Y-chromosome material renders the patient at i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
100
0
16

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 49 publications
(82 reference statements)
0
100
0
16
Order By: Relevance
“…Thus, gonadectomy could be postponed in patients who are reluctant to have surgery. This recommendation should be taken with caution, as other studies have shown higher rates of malignancy in such patients, and there are no established guidelines for monitoring them for development of malignancy if they choose not to undergo gonadectomy [McCann-Crosby et al, 2014].…”
Section: Discussionmentioning
confidence: 96%
“…Thus, gonadectomy could be postponed in patients who are reluctant to have surgery. This recommendation should be taken with caution, as other studies have shown higher rates of malignancy in such patients, and there are no established guidelines for monitoring them for development of malignancy if they choose not to undergo gonadectomy [McCann-Crosby et al, 2014].…”
Section: Discussionmentioning
confidence: 96%
“…The incidence of yolk sac elements with gonadoblastoma is found to be 10% of all the cases of malignant germ cell tumours associated with gonadoblastoma [5]. Gelincik et al [7] described one case of bilateral gonadoblastoma coexistent with dysgerminoma on one side and dysgerminoma and yolk sac tumour on the other side in a 10 year old girl with 46XX karyotype.…”
Section: Discussionmentioning
confidence: 99%
“…Only 2 cases of gonadoblastoma have been reported in normal male patients with scrotal testicles [5]. Gonadoblastoma coexistent with yolk sac tumour has been reported in a patient having female phenotype [6].…”
Section: Introductionmentioning
confidence: 99%
“…We found gonadoblastoma in all our patients when the shape of the gonad deviated from the expected streak-like shape . Gonadoblastoma is not a malignant tumor, but progression to dysgerminoma occurs at a high rate [McCann-Crosby et al, 2014].…”
Section: Common Findings In Laparoscopymentioning
confidence: 99%